Waqf Optimization in Aceh Province - Syahputra, Angga; Taufiq, Taufiq (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2022)
Aceh is noted to have extensive waqf land spread over 16,560 districts and cities with an area of ​​8,902.33 ha. Unfortunately, Aceh's waqf resources are relatively passive and have not been utilized optimally. Aceh even ranks as the poorest province in Sumatra, according to a release issued by BPS in 2020. Various waqf problems make the existing potential not adequately managed, even though if optimized, the benefits will be huge for the people of Aceh. For this reason, this study aims to investigate further waqf in Aceh Province so that it can be more optimal in its management and help improve the economy of the Acehnese people. This study uses a qualitative method where the data comes from a literature study obtained from good books, journals, articles, and websites. The results of this study indicate that the optimization of waqf in Aceh can work if stakeholders can improve overall community literacy, certify waqf land, provide guidance to waqf nadzir and make institutional improvements. With the advancement of these four things, it is believed that the potential of waqf in Aceh can be optimized and more productive to bring economic change to the people of Aceh. The implication of this research are recommends a major waqf literacy program, faster land certification, nadzir professionalism, and institutional reform of waqf management.